APLIKASI PEMBAYARAN SPP BERBASIS ANDROID DI MADRASAH ALIYAH WALISONGO LAMPUNG TENGAH - Helmiyanto Helmiyanto; Muhamad Muslihudin (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2020)
CET (Contributions Education Training) is funds have paid for students who will be used to education training. The size of the contribution education training must be paid by different for each class. Lack of information payments the parent barrier communication on payment in schools especially CET payments. Data processing manual pretty complicated and take a long time. Based on these problems them application CET payments android based in Islamic Senior High School Walisongo. This research using data collection method of observation and interview and in the design an application it uses the SDLC (System Development Life Cycle). The research is be a an application CET payments android based later application is expected to assist and loosening students, parents other users in the process of contribution education training payments in Islamic Senior High School Walisongo Lampung Central and can help officers administration until the schools in The registration of payment data CET to be more accurate and efficient.